Faktor-Faktor Yang Mempengaruhi Loyalitas Anggota Dojang Di Yogyakarta - Petra Surya Mega Wijaya; Maklon Haiti (HOME, 2021)
The development of dojang in Yogyakarta shows a pleasant increase because of the increasing number of taekwondo matches on a regional, national and even international scale followed by a large number of dojangs in Yogyakarta. This makes the members of the dojang to compete with each other and even move from one dojang to another because they see that the other dojang is superior to the dojang he is currently attending. This study aims to examine a number of variables that affect the loyalty of dojang members, including (1) brand image, (2) brand then, (3) satisfaction, (4) servqual, and (5) brand credibility. To answer the research objectives, 100 questionnaires were distributed randomly to a number of large dojang in Yogyakarta. The analytical tool used is multiple linear regression. The results showed that there were 2 variables that significantly or strongly influenced the loyalty of dojang members, namely (1) brand image, and (2) servqual. While there are 3 variables that do not significantly affect the loyalty of dojang members, namely (1) brand trust, satisfaction, and (3) brand credibility.